Procalcitonin as marker of the severity of sepsis in critically ill children - Deepashree, G; Rao, Chandrika; Rau, A T K (Indian Journal of Child Health, 2016)
Objective: To assess the role of procalcitonin (PCT) in the diagnosis and prognosis in children with sepsis. Design: Prospective, observational study. Setting: Tertiary care center in South India. Participants: Children, 1 month to 15 years of age, admitted with the diagnosis of sepsis excluding children with chronic systemic/inflammatory disease, degenerative neurologic disease, primary/ acquired immune deficiency, on steroids and children who had trauma/burns. Intervention: None. Main Outcome Measures: SerumPCT levels, grades of sepsis and mortality. Results: Respiratory tract infection was the most common source of sepsis (71%). Of the 53 patients studied, PCT was >2 ng/ml in 42 (79.2%) patients. Mean PCT values were 9.63, 17.72, and 84.68 ng/ml in sepsis, severe sepsis, and septic shock, respectively. PCT was found to be 86.36% sensitive, 55.56% specific with a positive predictive value (PPV) of 90.48, and negative predictive value of 45.45. 79.2% of patients in the study were discharged and 18.9% died. PCT levels were high in children who died subsequently. Conclusions: There is a positive association between PCT levels and the severity of sepsis as reflected by high sensitivity and PPV. High PCT levels also indicate increased chances of mortality.